Ultra-Broadband Sound Absorbing Materials Based on Periodic Gradient Impedance Matching - Wu, Fei; Zhang, Xiao; Ju, Zegang; Zhao, Jiang; Hu, Man; Gao, Mingyuan; Luo, Jun; Pu, Huayan (Frontiers in Materials, 2022)
Ultra-broadband sound absorption with periodic gradient impedance matching is of great concern in research of acoustic materials. This paper investigates the impedance matching of composite acoustic metamaterials composed of micro-perforated plates and subsequent Fabry-Pérot(FP) channels. Based on the impedance matching theory, ultra-broadband sound absorption has been realized through a design with 36 channels whose thickness is only 50mm. Also, the average sound absorption coefficient of 88% and an absorption frequency bandwidth (490-4000hz) can be achieved by preserving the matching impedance. Furthermore, in changing the thickness of the perfect absorber being 100mm, the average sound absorption coefficient can reach greater than 90% in the frequency range of 250-4500hz. The proposed structure is validated analytically and experimentally. This work can help with the designing and improving method of acoustic metasurface and especially have the potentials in ultra-broadband sound absorbers design.